Nilai Perusahaan di Indonesia: Sebuah Analisis Bibliometrik - Adi Saputra, Dany; Nur Ardila, Lina; Jannah, Miftahul (Universitas Jember, 2025)
This bibliometric study identifies important patterns and advances in the literature on Indonesian firm value. Understanding the ways in which different variables affect business value in this emerging market is becoming more important, as evidenced by the growing body of research. Through the analysis of publishing patterns and identification of specific findings in the Indonesian context, this study offers insightful recommendations for further research aimed at improving our understanding of the dynamics of firm value in Indonesia. According to the results of the investigation, a number of important elements, such as corporate governance, profitability, and corporate social responsibility, have a significant impact on firm value. From 2012 to 2024, the publication patterns of Indonesian firm value emphasize important conclusions from a number of assessments and bibliometric studies. This study concentrates on firm value-related factors, emerging literature trends, and cross-disciplinary problem areas. Understanding Indonesian firm value research begins with this bibliometric study. This study offers new research avenues to better understand how Indonesian organizations generate and preserve value by identifying important themes and underexplored areas. Focusing on the development of determinants, sector-specific research, and comparative analysis can help academics and practitioners make better judgments about corporate value in Indonesia. This study can expand the literature on corporate value in Indonesia and contribute to the discussion of corporate performance and value creation in developing countries. Keywords: Bibliometric, Firm Value, Trend Analysis, Indonesia